Assessing proprioceptive acuity in people with multiple sclerosis. Issue 3 (July 2022) - Goldlist, Serena; Wijeyaratnam, Darrin O; Edwards, Thomas; Pilutti, Lara A; Cressman, Erin K
Background: Proprioceptive acuity and impairments in proprioceptively guided reaches have not been comprehensively examined in people with multiple sclerosis (MS). Objective: To examine proprioceptive acuity in people with MS who self-report and who do not self-report upper limb (UL) impairment, and to determine how people with MS reach proprioceptive targets. Methods: Twenty-four participants with MS were recruited into two groups based on self-reported UL impairment: MS-R (i.e. report UL impairment; n   =  12) vs. MS-NR (i.e. do not report UL impairment; n   =  12). Proprioception was assessed using ipsilateral and contralateral robotic proprioceptive matching tasks. Results: Participants in the MS-R group demonstrated worse proprioceptive acuity compared to the MS-NR group on the ipsilateral and contralateral robotic matching tasks. Analyses of reaches to proprioceptive targets further revealed that participants in the MS-R group exhibited deficits in movement planning, as demonstrated by greater errors at peak velocity in the contralateral matching task in comparison to the MS-NR group. Conclusion: Our findings suggest that people with MS who self-report UL impairment demonstrate worse proprioceptive acuity, as well as poorer movement planning in comparison to people with MS who do not report UL impairment.